2017
DOI: 10.3390/nu9070660
|View full text |Cite
|
Sign up to set email alerts
|

The Diuretic Action of Weak and Strong Alcoholic Beverages in Elderly Men: A Randomized Diet-Controlled Crossover Trial

Abstract: With ageing, there is a greater risk of dehydration. This study investigated the diuretic effect of alcoholic beverages varying in alcohol concentration in elderly men. Three alcoholic beverages (beer (AB), wine (AW), and spirits (S)) and their non-alcoholic counterparts (non-alcoholic beer (NAB), non-alcoholic wine (NAW), and water (W)) were tested in a diet-controlled randomized crossover trial. For the alcoholic beverages, alcohol intake equaled a moderate amount of 30 g. An equal volume of beverage was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…It is possible that alcohol consumption may have diuretic action and influence dehydration; however, the extent of these effects is not fully understood. A previous RCT study showed that spirits (consumed at an amount similar to our study) caused only a small and transient diuretic effect at 4 h, and that there were no differences in 24 hr urine output or urine osmolarity when compared to subjects that consumed water [30]. Another study reported that more urine was excreted after 4 h when beer (4% alcohol), compared to the non-alcoholic beverage, was consumed during euhydration (p < 0.001), while there was no significant difference between groups during hypohydration (p = 0.06) [31].…”
Section: Discussionsupporting
confidence: 71%
“…It is possible that alcohol consumption may have diuretic action and influence dehydration; however, the extent of these effects is not fully understood. A previous RCT study showed that spirits (consumed at an amount similar to our study) caused only a small and transient diuretic effect at 4 h, and that there were no differences in 24 hr urine output or urine osmolarity when compared to subjects that consumed water [30]. Another study reported that more urine was excreted after 4 h when beer (4% alcohol), compared to the non-alcoholic beverage, was consumed during euhydration (p < 0.001), while there was no significant difference between groups during hypohydration (p = 0.06) [31].…”
Section: Discussionsupporting
confidence: 71%
“…The fermentation process may also be beneficial for reducing bacterial concentration of water, thereby potentially providing a safer form of hydration (Rosinger & Bethancourt, 2020). High concentrations of alcohol, on the other hand, may have at least small, acute diuretic effects (Polhuis, Wijnen, Sierksma, Calame, & Tieland, 2017), and this may explain why we observed an increased odds of concentrated urine among Daasanach men who reported consuming liquor in the previous week.…”
Section: Discussionmentioning
confidence: 83%
“…It seems that a moderate consumption of low-grade alcoholic beverages, such as beer, do not compromise HS. However, an increase of either the dose or the alcohol content, may worsen hypohydration [28]. Similarly, caffeinated drinks as well its diuretic effects could also lead to hypohydration.…”
Section: Introductionmentioning
confidence: 99%